Konstruksi Citra Joko Widodo dalam Sampul Majalah Milenial Arrajol, Arab Saudi, Edisi 20 Mei 2019 - Hendro Eko Setiawan (Al-Ma‘rifah, 2020)
Indonesian President Joko Widodo is widely discussed on social media because he was chosen as the cover story in Arrajol, a monthly Arabic men’s lifestyle magazine published in Saudi Arabia. On its official Facebook page, Arrajol displays a promotional video of their latest edition by writing, “President of Indonesia, a figure in the new edition of Arrajol magazine.” The video was uploaded by Arrajol on Thursday, May 16, 2019. The purposes of this study are to determine the symbol contained in Arrajol, the meaning contained within the symbol, and how these symbols constructing Joko Widodo’s image as a role model. This study uses qualitative methods with semiotics analysis from Charles Sanders Peirce. The result of this study showed Arrajol magazine consists of two main symbols, the gesture symbol of Joko Widodo who is dressed in a suit with a thin smile on his face, is Joko Widodo’s authority, and followed by the text on the bottom right showing Joko Widodo’s personality. These symbols have different meanings. The meaning contained in each symbol constructs the image of Joko Widodo as a model for the world community.